2012
DOI: 10.4269/ajtmh.2012.12-0086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Chagas Disease in Pregnant Women in Casanare, Colombia

Abstract: Abstract. Knowledge of the prevalence and risk factors associated with maternal infection is the first step to develop a surveillance system for congenital transmission of Chagas disease. We conducted a cross-sectional study in Casanare, a disease-endemic area in Colombia. A total of 982 patients were enrolled in the study. A global prevalence of Trypanosoma cruzi infection of 4.0% (95% confidence interval [CI] = 2.8-5.3%) was found. Multivariate analysis showed that the most important risk-associated factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
5
18
2
3
Order By: Relevance
“…This may be related to the impact of previously implemented primary measures of control of transmission in this population, and is in agreement with the observation of an age >29 years as a risk factor for the infection in pregnant women in a recently published study in the same population [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This may be related to the impact of previously implemented primary measures of control of transmission in this population, and is in agreement with the observation of an age >29 years as a risk factor for the infection in pregnant women in a recently published study in the same population [12].…”
Section: Discussionsupporting
confidence: 91%
“…Later, a study involving the analysis of infected vectors and their presence in housings that showed this region as the one with the highest risk of disease transmission in Colombia [26]. More recently, a study found a prevalence of 4% of infection among pregnant women and 9.3% among their relatives in the same population [12]. Hence, it is of great importance to implement well-organized surveillance strategies in this population, in order to the prompt detection of infected people, and most importantly, the implementation of a follow up program for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies investigated the use of several potential determinants of Chagas disease, such as recognizing the kissing bug or reporting living in places with kissing bugs (22) (23) (24) (25) (26) (27) , previous knowledge of the vector (28) (29) , reporting being bitten by the kissing bug (24) , reporting living in mud houses or in rural areas (22) (23) (28) (29) (30) (31) , Latin America as a place of birth or destination of previous travel (22) (32) , reporting receiving blood transfusions in the past (27) (33) , reporting blood donations in the past (26) (30) , education (22) (28) (30) (33) , social condition or income (22) (30) , reporting siblings or relatives with Chagas disease (23) (26) (27) , sex (26) (31) , and age (26) (28) (30) (31) (33) . However, they were all investigated under different conditions (blood bank screening, vertical transmission screening, and in rural area inhabitants) for different purposes, resulting in substantially different results from this research.…”
Section: Discussionmentioning
confidence: 99%